2018
DOI: 10.31878/ijcbr.2018.44.05
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effect of Incentive Spirometry on Arterial Blood Gases Analysis After Coronary Bypass Graft Surgery Patients

Abstract: Background: The patients who have done CABG are prone to pulmonary complications. Various physiotherapy management is present for prevention of lung complication. Literature shows lots of technique as treatment of choice, incentive spirometry is one of them. AIM: To asses immediate effect of incentive spirometry on arterial blood gas analysis in patient recently underwent coronary artery bypass surgery. Method: There was 30 patients. Blood was drawn from arterial line for pre-treatment ABG. Incentive spirometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The results of another study showed that incentive spirometry is signi cantly effective in improving the arterial blood gas parameters [17]. Another study showed that incentive spirometry led to a signi cant improvement in PaO 2 and SaO 2 and a decrease in PaCO 2 in patients undergoing CABG [18]. The discrepancy in the ndings can be related to the differences in the pattern of breathing exercises used in the studies in terms of the frequency and duration of breathing exercises; as well as combining breathing exercises with other routine respiratory care.…”
Section: Discussionmentioning
confidence: 99%
“…The results of another study showed that incentive spirometry is signi cantly effective in improving the arterial blood gas parameters [17]. Another study showed that incentive spirometry led to a signi cant improvement in PaO 2 and SaO 2 and a decrease in PaCO 2 in patients undergoing CABG [18]. The discrepancy in the ndings can be related to the differences in the pattern of breathing exercises used in the studies in terms of the frequency and duration of breathing exercises; as well as combining breathing exercises with other routine respiratory care.…”
Section: Discussionmentioning
confidence: 99%